Interventions to increase participation of NGOs in preventive care: A scoping review - Haniye Sadat Sajadi; Laleh Ghadirian; Fatemeh Rajabi; Azadeh Sayarifard; Narges Rostamigooran; Reza Majdzadeh (Health Science Reports, 2022)
Abstract Background and Aims Nongovernmental organizations (NGOs) have enormous potential to effectively prevent and manage diseases; however, little research is available on interventions used to improve NGOs' participation in this area. A scoping review was conducted to identify options proposed or implemented to improve the participation of the NGOs in preventive care. Methods Pubmed, Web of Science, and ProQuest were extensively searched. Google Scholar was also searched to find potential studies related to the subject. Relevant keywords were used in the English language. The reference list of relevant studies was also scanned. Studies were screened with defined inclusion and exclusion criteria. Relevant data were then extracted. Two individuals independently screened and extracted studies. The interventions implemented or proposed to promote the participation of the NGOs in the implementation of preventive interventions were deductively identified and classified. Results Eighteen articles were included in our review. We identified 31 interventions and categorized them into 11 strategies, including (1) building strong collaboration among NGOs and with governments; (2) expanding networks and sustained relations among NGOs; (3) evaluating the NGOs' performance; (4) increasing intersectoral collaboration; (5) advocating for the role of NGOs; (6) supporting NGOs from the side of government; (7) empowering the abilities and capabilities of NGOs; (8) defining the precise roles and responsibilities of the parties; (9) strengthening the health system governance; (10) increasing the health literacy of the community; and (11) developing required regulations, rules, and policies. None of the interventions identified had evidence of its effectiveness. Conclusion The current evidence on effective interventions to strengthen NGOs' participation in implementing health care is scanty. It means there is an information gap in the effect of interventions to improve NGOs' participation in health.